Kebijaksanaan dan Kesaktian dalam Cerita Rakyat Datu Langko sebagai Model Kepemimpinan dalam Budaya Sasak - Nurul Haeniah; Disa Arliwan; Andi Saadilah; Kadirun Kadirun; Samsuddin Samsuddin (Universitas Nahdlatul Wathan Mataram, 2026)
This study aims to examine the representation of wisdom and supernatural power in the character of Datu Langko as a model of ideal leadership in the Datu Langko folktale, which originates from the oral tradition of the Sasak people in West Nusa Tenggara. This study employs a descriptive qualitative approach using narrative analysis to examine the construction of the character within the text and the meaning of the leadership values represented. The data, consisting of the folklore text, was analyzed through the stages of reduction, categorization, interpretation, and drawing conclusions, referencing cultural leadership theory and oral literature studies. The research findings indicate that Datu Langko’s wisdom is reflected in self-awareness, responsibility, respect for others’ opinions, the ability to set priorities, the ability to make sound decisions, and a strong sense of religiosity. Meanwhile, the aspect of supernatural power is manifested through the ability to interact with supernatural beings, utilizing supernatural forces for collective benefit, and the use of incantations within ritual contexts. These findings indicate that in Sasak culture, ideal leadership is understood as a fusion of intellectual, moral, and spiritual capacities. The novelty of this study lies in revealing the integration of wisdom and supernatural power as a unified construct of cultural leadership within Sasak folklore, which has previously tended to be studied descriptively and in isolation. Theoretically, this study contributes to the development of oral literature studies and the representation of leadership from a cultural perspective, as well as enriches the use of folklore as a source of values education in the fields of education, language, and literature. Keywords: folklore, Datu Langko, wisdom, supernatural power, oral literature